2021
DOI: 10.3390/nu13072231
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Risk of Rheumatoid Arthritis among Chinese Adults: A Prospective Study

Abstract: Alcohol consumption may be associated with the risk of rheumatoid arthritis (RA), but potential sex-related differences in this association have not been explored. Thus, we utilized 87,118 participants in the Kailuan Study, a prospective cohort initiated in 2006 to study the risk factors of cardiovascular disease in a Chinese population. We included those that did not have RA at baseline (2006), and performed cox proportional hazard modeling to calculate the hazard ratio (HR) and 95% confidence interval (95% C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Environmental factors such as cigarette smoking, air pollution, occupational exposure, as well as dietary factors, are aligned with RA development (7). Among dietary factors, intake of red meat and alcohol consumption are positively associated with the risk of RA (8,9), while higher consumption of fruits, vegetables, fish, as well as antioxidants, are inversely associated with the risk (10). Recently, the antioxidant properties of tea and coffee and their relation to the progression of RA has been taken into consideration (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors such as cigarette smoking, air pollution, occupational exposure, as well as dietary factors, are aligned with RA development (7). Among dietary factors, intake of red meat and alcohol consumption are positively associated with the risk of RA (8,9), while higher consumption of fruits, vegetables, fish, as well as antioxidants, are inversely associated with the risk (10). Recently, the antioxidant properties of tea and coffee and their relation to the progression of RA has been taken into consideration (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Our question of whether this could be a missed insidious late presentation was answered by the normal bilateral hand x-rays that did not show erosions, suggesting that this case was an acute onset of disease rather than a chronic ongoing process. Although the patient's alcohol use preceded the onset of disease, the literature on the association of alcohol and risk of RA is inconclusive with mixed evidence of increased, decreased and in some studies showing no association [6] [7] [8]. Furthermore, only few cases of RA initially presenting with pleural and/or pericardial effusion have been reported, however, of those that have, all patients complained of chest pain and/or shortness of breath [9] [10] [11] [12].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in an observational study of 16,762 individuals, Baker et al showed no protective effect of alcohol consumption after excluding the confounding factors [44]. Another prospective study in a Chinese cohort discovered that drinking alcohol increased the risk of women developing RA [45].…”
Section: Alcohol Intakementioning
confidence: 90%